Stomach cancer and work in dusty industries. Issue 5 (May 1990) - Coggon, D; Barker, D J; Cole, R B
Abstract : The city of Stoke-on-Trent, whose major industries include coalmining, iron and steel, ceramics, and rubber, has death rates from stomach cancer some 80% above the national average. To explore the hypothesis that work in these dusty industries is responsible for the local excess of stomach cancer, we compared 95 incident cases with 190 age and sex matched community controls. Lifetime occupational histories and premorbid consumption of foods suspected of causing or protecting against stomach cancer were ascertained by a self administered questionnaire, supplemented at interview. Sixty eight cases had at some time held a manual job in one of the four dusty industries (relative risk = 1.4, 95% confidence interval 0.8-2.4). After allowance for diet, rubber manufacture was the industry most strongly associated with stomach cancer (relative risk = 2.5, 95% CI 1.0-6.4). Associations were also found with coal mining and ceramics but these were not statistically significant at a 5% level. The estimated proportion of stomach cancer attributable to the four dusty industries was 23%. It is concluded that the high incidence of stomach cancer in Stoke-on-Trent is unlikely to be explained solely by occupational exposure to dust.